2020
DOI: 10.1371/journal.pbio.3000648
|View full text |Cite
|
Sign up to set email alerts
|

Eomes broadens the scope of CD8 T-cell memory by inhibiting apoptosis in cells of low affinity

Abstract: The memory CD8 T-cell pool must select for clones that bind immunodominant epitopes with high affinity to efficiently counter reinfection. At the same time, it must retain a level of clonal diversity to allow recognition of pathogens with mutated epitopes. How the level of diversity within the memory pool is controlled is unclear, especially in the context of a selective drive for antigen affinity. We find that preservation of clones that bind the activating antigen with low affinity depends on expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
(103 reference statements)
3
27
0
Order By: Relevance
“…Moreover, extensive work using APLs to stimulate naïve CD8 + T cells in multiple murine TCR transgenic systems showed that, starting from approximately 1 day after activation, T cells express IRF4 in a graded manner, reflecting stimulation strength [55][56][57][58]. As IRF4 can enhance effector differentiation [57,58], this suggests that subtle tuning of gene expression during the early days of naïve T cell activation might alter differentiation outcomes, as has been observed in in vivo models for both CD4 + and CD8 + T cells [47,[67][68][69][70][71][72]. Similarly, experiments stimulating murine CD4 + T cells with varying antigen doses found that, after 24 h, stimulation strength correlated with the expression of IL-12Rβ2, which facilitates Th1 polarization in response to IL-12 signaling [72].…”
Section: Trends In Immunologymentioning
confidence: 87%
“…Moreover, extensive work using APLs to stimulate naïve CD8 + T cells in multiple murine TCR transgenic systems showed that, starting from approximately 1 day after activation, T cells express IRF4 in a graded manner, reflecting stimulation strength [55][56][57][58]. As IRF4 can enhance effector differentiation [57,58], this suggests that subtle tuning of gene expression during the early days of naïve T cell activation might alter differentiation outcomes, as has been observed in in vivo models for both CD4 + and CD8 + T cells [47,[67][68][69][70][71][72]. Similarly, experiments stimulating murine CD4 + T cells with varying antigen doses found that, after 24 h, stimulation strength correlated with the expression of IL-12Rβ2, which facilitates Th1 polarization in response to IL-12 signaling [72].…”
Section: Trends In Immunologymentioning
confidence: 87%
“…By regulating different AKT protein isoforms with different PIP3 levels, diversified downstream signaling pathways were activated and led to alternative cell fate 65 . When the cumulative signal intensity is appropriate, Tscm can be maximally induced 66 . The ratio of PI(4,5)P2 and PIP3 has been demonstrated to be a quantitative measurement for TCR signal strength.…”
Section: Regulations Of Tcr and Costimulatory Signalsmentioning
confidence: 99%
“…Interestingly, this induction is stronger under submaximal TCR stimulation [ 62 ]. Also, in vivo submaximal TCR affinity results in the highest EOMES upregulation and drives central memory formation [ 76 ]. Besides IL-4, type 1 interferons (IFNs) can also induce EOMES expression as is shown by the reduced EOMES levels in T AIM cells lacking the receptor or signaling pathway required for type 1 IFN pathway.…”
Section: Key Epigenetic and Transcriptional Regulators In T Aim Differentiationmentioning
confidence: 99%
“…EOMES is required for T AIM differentiation at several levels. EOMES has been shown to bind directly to the promotor and internal regions of Bcl2 and drive Bcl2 expression (pro-survival protein), thereby giving memory cells a survival advantage compared to the strongly stimulated effector cells [ 76 ]. Besides driving pro-survival signals, EOMES is also involved in upregulation of CD122, which is part of the IL-15 receptor and upregulated in T AIM cells [ 15 , 29 , 34 , 37 ].…”
Section: Key Epigenetic and Transcriptional Regulators In T Aim Differentiationmentioning
confidence: 99%